1986
DOI: 10.1029/ja091ia08p08937
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of oxygen permitted line emissions by SF6 injection into the F region

Abstract: The use of SF6 releases to excite the airglow from atomic oxygen in the ionosphere is demonstrated by experiment and by theory. Enhanced 777.4‐nm emissions from O(5P) states were measured during the AFGL‐sponsored Ionospheric Modification Studies campaign at Wallops Island, Virginia. For this rocket campaign, 8×1025 molecules of SF6 were released at 350‐km altitude into the midnight ionosphere on November 9, 1983. The 777.4‐nm airglow increased by over 150 R. The temporal evolution of the airglow is simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 31 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The first SF 6 releases were done as part of Project Firefly in the 1960s . Since then, SF 6 has been released as part of the Ionospheric Modification Studies (IMS) campaign in 1983, , the Space Plasma Negative Ion Experiments (SPINEX-1 and -2) in 1984 and 1986, , the CRRES-at-Kwajalein campaign in 1990, , in three rockets launched from the Russian research vessel Professor Vize in 1988, , and in trace amounts from a rocket carrying a negative ion mass spectrometer for mass calibration . SF 6 was also used in an experiment to measure the very low free electron concentrations in the lower ionosphere.…”
Section: Active Chemical Release Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first SF 6 releases were done as part of Project Firefly in the 1960s . Since then, SF 6 has been released as part of the Ionospheric Modification Studies (IMS) campaign in 1983, , the Space Plasma Negative Ion Experiments (SPINEX-1 and -2) in 1984 and 1986, , the CRRES-at-Kwajalein campaign in 1990, , in three rockets launched from the Russian research vessel Professor Vize in 1988, , and in trace amounts from a rocket carrying a negative ion mass spectrometer for mass calibration . SF 6 was also used in an experiment to measure the very low free electron concentrations in the lower ionosphere.…”
Section: Active Chemical Release Experimentsmentioning
confidence: 99%
“…They did not model the concentrations of SF 6 – and SF 5 – separately, but suggested that SF 6 – is the major ion formed. Bernhardt extended the analysis by arguing that ionospheric temperatures are too high and collision frequencies too low to allow formation of SF 6 – as the primary negative ion. He predicted that SF 5 – should be the major negative ion formed and that the production rate of SF 6 – should be negligible.…”
Section: Active Chemical Release Experimentsmentioning
confidence: 99%
“…These experimental observations have prompted new theoretical and numerical simulation modeling efforts since past work had primarily considered the depletion evolution on large space and timescales. These early works considered electron attachment and neutralization chemistry, airglow production, macroscopic electrodynamics, and macroscopic plasma instabilities [Mendillo and Forbes, 1982;Bernhardt, 1984Bernhardt, , 1986Bernhardt, , 1988Bernhardt et al, 1991; Scales and Bernhardt, 1991]. Our earlier theoretical and simulation work [Ganguli et al, 1992;Scales et al 1992, 19944] was the first attempt to consider the early time microscopic processes associated with chemically produced electron depletions.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the complex processes that can occur in a gas release, numerous models have been developed over the years to study various aspects of a gas release. With regard to macroscopic modeling there have been chemical models [Sjolander and Szuszczewicz, 1979;Yau et al, 1985;Bernhardt et al, 1986], one-dimensional field-aligned diffusion models [Bernhardt, 1987; Schunk, 1990], and recently, some simplified three-dimensional models [ Voskoboynikov et al, 1987;Zalesak et al, 1988]. In addition, there have been small-scale particle-in-cell and Vlasov-Poisson simulations of expanding plasma clouds to study cross-field streaming characteristics [Galvez, 1987;Winske, 1988], field-aligned plasma expansion [Schunk and Szuszczewicz, 1988], and critical ionization velocity processes [e.g., Machida and Goertz, 1986, and references therein].…”
Section: Introductionmentioning
confidence: 99%